Diversity of earthworms (Clitellata: Lumbricidae) from Sredna Gora Mountain (Bulgaria) - Valchovski, H. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2016)
In the current study the diversity, zoogeographical position and distribution of earthworms from Sredna Gora Mountain (Bulgaria) is presented. During the present investigation, altogether ten earthworm species belonging to seven genera were collected. Among them, seven taxa are reported for the first time from the Sredna Gora Mt.: Cernosvitovia rebeli, Dendrobaena alpina, Allolobophoridella eiseni, Dendrodrilus rubidus rubidus, Aporrectodea caliginosa, Aporrectodea rosea and Lumbricus terrestris. On the basis of the new and literature data here we provide the first list of lumbricid earthworms from Sredna Gora Mountain.